1992
DOI: 10.1016/0035-9203(92)90441-e
|View full text |Cite
|
Sign up to set email alerts
|

Differential cellular reactivity to adult worm antigens of patients with different clinical forms of schistosomiasis mansoni

Abstract: Analysis of the proliferation in vitro of peripheral blood mononuclear cells and the production of interferon-gamma (IFN-gamma) in individuals infected with Schistosoma mansoni and showing different clinical forms of the disease, as well as normal putatively immune individuals from an endemic area, was undertaken using total and fractionated soluble adult worm antigens (SWAP). A higher frequency of detectable response to fractionated antigens in T cell Western blot assays was observed in individuals with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…Analysis of IFN-γ secretion in supernatants of tissue cultures demonstrated that, as described for the INT group, very low to undetectable levels of this cytokine are secreted in PBMC cultures stimulated with the parasite antigens (24).…”
Section: Hepatosplenic Form Of Schistosomiasismentioning
confidence: 61%
“…Analysis of IFN-γ secretion in supernatants of tissue cultures demonstrated that, as described for the INT group, very low to undetectable levels of this cytokine are secreted in PBMC cultures stimulated with the parasite antigens (24).…”
Section: Hepatosplenic Form Of Schistosomiasismentioning
confidence: 61%
“…29 Moreover, when stimulated with Schistosoma antigens, peripheral blood mononuclear cells (PBMC) of EN persons proliferate vigorously and produce higher levels of IFN-g than those of persons currently infected and those resistant to reinfection. 28,30,31 On the basis of this evidence, it appears that Th1 and Th2 immune response are involved in protection against the infection in this naturally resistant group of persons.…”
Section: Introductionmentioning
confidence: 92%
“…It is not yet clear whether this observed pattern is the result of changes in behavior or acquired immunity as the endemic population ages. 1,2 Recently, both Webster and coworkers 3 and our group 4,5 have reported that another rise in infection intensity occurs among the elderly, suggesting a loss of this partially acquired immunity by aged people. To date, there has been no systematic study of the immune response of individuals residing in S. mansoni endemic areas over the age of 60 years.…”
Section: Introductionmentioning
confidence: 99%